Abrasive wear behaviour of ADI material with various retained austenite content. (3rd July 2016) - Balos, S.; Rajnovic, D.; Dramicanin, M.; Labus, D.; Eric-Cekic, O.; Grbovic-Novakovic, J.; Sidjanin, L.
Abstract : In this paper, the wear rate of ferritic and pearlitic ductile iron, as well as three types of austempered ductile iron (ADI materials), austempered at 300, 350 and 400 °C is investigated. Two wear parameters were varied, wear load (0.5, 1.3, 2 kg) and grit paper abrasive grain size (P240, P500, P800). The hardness of ductile iron and stress-assisted phase transformation of retained austenite into martensite (SATRAM) phenomenon in ADI materials were found to play major roles in wear behaviour. The pronounced SATRAM phenomenon was detected for the most severe wear parameters. Another important factor in the occurrence of SATRAM phenomenon is the presence of metastable, low carbon-enriched retained austenite. As a consequence, the wear rate of ADI austempered at 400 °C is nearly equivalent to ADI austempered at 300 °C at medium and high loading with the coarsest abrasive paper grit tested (P240).